2020
DOI: 10.1002/jcp.29757
|View full text |Cite
|
Sign up to set email alerts
|

miR‐506‐3p alleviates uncontrolled osteoclastogenesis via repression of RANKL/NFATc1 signaling pathway

Abstract: Bone erosion is the major cause of deformities in autoimmune disease conditions such as osteoporosis and rheumatoid arthritis. Aberrant receptor activator of nuclear factor kappa B ligand (RANKL) secretion in bone disorders have been implicated to promote uncontrolled osteoclast differentiation through the regulation of nuclear factor of activated T cells 1 (NFATc1) transcription factor. This phenomenon is governed by several molecular factors including microRNAs, which are under‐expressed during disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In vitro experiments showed that miR-128 may play a regulatory role in BMMs through miR-128/SIRT1/NF-kB signaling axis, and over expression or inhibition of miR-128 can significantly increase or decrease the occurrence of macrophage-derived osteoclasts, respectively (Shen et al, 2020). Further studies found that miR-506-3p can selectively inhibit NFATc1 in RANKL-induced activated rat BMMs, further reduce the release of bone resorption enzymes, thus relieving osteolysis (Dinesh et al, 2020). What's more, both the smo-GLI1/2 axis (Hh ligands permitting the activation of Hh signal transducer smoothened (SMO) and transmitting intracellular signaling through transcription factors of the GLI family)in the Hedgehog (Hh) signaling pathway (Kohara et al, 2020) and delphinidin (Imangali et al, 2020) can mediate the regulation of osteoclasts by macrophages.…”
Section: Osteoporosismentioning
confidence: 99%
“…In vitro experiments showed that miR-128 may play a regulatory role in BMMs through miR-128/SIRT1/NF-kB signaling axis, and over expression or inhibition of miR-128 can significantly increase or decrease the occurrence of macrophage-derived osteoclasts, respectively (Shen et al, 2020). Further studies found that miR-506-3p can selectively inhibit NFATc1 in RANKL-induced activated rat BMMs, further reduce the release of bone resorption enzymes, thus relieving osteolysis (Dinesh et al, 2020). What's more, both the smo-GLI1/2 axis (Hh ligands permitting the activation of Hh signal transducer smoothened (SMO) and transmitting intracellular signaling through transcription factors of the GLI family)in the Hedgehog (Hh) signaling pathway (Kohara et al, 2020) and delphinidin (Imangali et al, 2020) can mediate the regulation of osteoclasts by macrophages.…”
Section: Osteoporosismentioning
confidence: 99%
“…Consequently, in highlighting the nature of these developing integrative regulatory networks, the next section is devoted to reviewing, a) which micro-RNAs are regulated by (or regulate) p53, and b) how these micro-RNAs regulate cathepsin protease family members in the context of cancer, with a view to broadening our understanding of the regulatory interplay between p53 and cathepsin transcription. Broadly speaking, miRNA-200c, miRNA-152 and miRNA-106b appear to be the most characterized in this context, with others such as miRNA-29a (cathepsin K, [55]), miRNA-30 (cathepsin D, [56]), miRNA-25-3p (cathepsin K, [57]), miRNA-140 (cathepsin B, [58]), miRNA-483-5p (cathepsin K, [59]) and miRNA-506-3p (cathepsin K, [60]) being characterized to a lesser extent (Table 2). The expression of micro-RNAs connected with cathepsin gene expression are highlighted in conjunction with specific p53 isoforms and cell types they have been collectively characterized in (WT-p53, wild-type p53; PBMC, Peripheral Blood Mononuclear Cells; -, unknown).…”
Section: P53 Micro-rna Regulation and Cathepsin Proteases: A Developing Networkmentioning
confidence: 99%
“…Up-regulated of miR-21 ( 82 ) which targets TET1 , reduce RA inflammation. Macrophage-derived exosomes miR-506-3p ( 84 ) and miR-103a ( 85 ) regulate the progression of RA by inhibiting the RANKL/NFATc1 signaling pathway and activating the JAK/STAT3 signaling pathway. miR-132 secreted by aryl hydrocarbon receptor activation Th17 in extracellular vesicles acts as a pro-inflammatory mediator to reduce the production of COX2 , to increase the production of osteoclast ( 86 ).…”
Section: Regulatory Roles Of Mirnas In Cells and Their Secretions Inv...mentioning
confidence: 99%